In vitro assay of Staphylococcus aureus enterotoxin A activity in food. - Rasooly, L (1997)
Staphylococcus aureus enterotoxin A (SEA) is a leading cause of food poisoning. The current test for functional activity of SEA requires monkeys or kittens. The major drawbacks of animal assays are lack of quantitation, poor reproducibility, low sensitivity, and high cost. In this report we describe and evaluate an alternative assay using T-cell proliferation to measure SEA activity in food. Human and rat lymphocytes proliferate in response to concentrations of SEA as low as 1 pg/ml, well below the pathogenic dose of 100 ng. This proliferation assay is highly sensitive, quantitative, and simple. Nonradioactive assays of T-cell proliferation were also suitable for detecting and measuring SEA, although with a 10-fold lower sensitivity. To evaluate the utility of this assay for food testing, four different food samples were mixed with SEA. In each sample, SEA was detected at a concentration of 1 ng/ml. Heat-inactivated SEA produced no detectable proliferation. These results demonstrate that an in vitro cell proliferation assay is an advantageous alternative to existing animal assays for measuring SEA activity in food.